Strategic construction waste management model for Contractors of large residential projects / Siti Merianna Awang Rosppa ... [et al.] - Awang Rosppa, Siti Merianna; Yunus, Julitta; Esa, Mohd Reza; Ramli, Siti Aishah (2021)
High generation of residential construction waste in Selangor resulting adverse problems to the environment and due to low recycling percentage and unmatured market of recycled materials, most of the waste generated is disposed to the landfill. Most contractors do not generally support waste management due to their profit-driven nature. Thus, urgent actions are needed to increase the adoption of effective construction waste management by the contractors. Since impractical waste management will give a huge impact on the environment, which later can affect human health and welfare, is it crucial to determine the critical consideration of adopting construction waste management by the industry players, especially contractors? This is crucial not only to promote a sustainable environment but also to integrate waste management infrastructure instead of a solid reliance on conventional landfilling practice. 209 Grade 7 Contractors in Selangor participated in this study. The data was obtained and analysed empirically and the correlation was verified with Kruskal-Wallis test. Three critical consideration factors: the employees' adequate construction waste management practices knowledge, negative impact on economic output, and the requirement to improve environmental performance by the client have to lead these research findings in highlighting to construction industry players to increase the strategies of adopting construction waste management. The significance of this research is by understanding the critical consideration factors to strategize the construction waste management practices. Hence, the effective model for construction waste management developed critically not only in the construction process but also in the design and planning process.